2021
DOI: 10.3345/cep.2021.00066
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical features and laboratory findings of coronavirus disease 2019 and influenza A and B infections in children: a single-center study

Abstract: Comparison of clinical features and laboratory findings of coronavirus disease 2019 and influenza A and B infections in children: a single-center studyRunning title: Clinical and laboratory findings of pediatric COVID-19 versus influenza patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
2
14
2
Order By: Relevance
“…Comparing these symptomatic infections, we found that pediatric disease presentation is very similar between endemic HCoVs and SARS-CoV-2, with each frequently presenting with “common cold” symptoms. Consistent with other studies, we found differences in symptom presentation by age; this may be, perhaps, because older children have had more endemic HCoV exposures [ 2 , 4 , 6 , 17 , 22 ]. We also found great variability in symptom duration for SARS-CoV-2 and endemic HCoV infections; symptoms from endemic HCoV and SARS-CoV-2 infections lasted anywhere from 1 day to more than 28 [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparing these symptomatic infections, we found that pediatric disease presentation is very similar between endemic HCoVs and SARS-CoV-2, with each frequently presenting with “common cold” symptoms. Consistent with other studies, we found differences in symptom presentation by age; this may be, perhaps, because older children have had more endemic HCoV exposures [ 2 , 4 , 6 , 17 , 22 ]. We also found great variability in symptom duration for SARS-CoV-2 and endemic HCoV infections; symptoms from endemic HCoV and SARS-CoV-2 infections lasted anywhere from 1 day to more than 28 [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Differences in immune response between adults and children likely provide children better protection against severe SARS-CoV-2 infections [ 3 5 ]. Previous research found no differences in severity between SARS-CoV-2 infections and influenza A and B among children [ 6 , 7 ]. However, it is unknown if, in children, SARS-CoV-2 infections are distinct in disease presentation and severity from endemic human coronavirus (HCoV) infections.…”
Section: Introductionmentioning
confidence: 93%
“…Siddiqui et al statistically confirmed that symptoms such as fever, cough, rhinorrhea, vomiting, and abdominal pain were greater in children with Influenza than in those with COVID-19. 21 Also, in this study, diarrhea was more frequent (but non-statistically significant) in the Influenza group than in the one with COVID-19, while headache was a symptom more frequently reported by children with COVID-19. 21 …”
Section: Resultscontrasting
confidence: 52%
“…A comparison of clinical features between COVID-19 and Influenza was reported in 11 of 12 studies. 10 – 17 , 19 21 …”
Section: Resultsmentioning
confidence: 99%
“…(35) Previous research found no differences in severity between SARS-CoV-2 infections and influenza A and B among children. (6, 7) However, it is unknown if, in children, SARS-CoV-2 infections are distinct in disease presentation and severity from endemic human coronavirus (HCoV) infections.…”
Section: Introductionmentioning
confidence: 99%